THE DIRECT METHOD IN ENGLISH LANGUAGE TEACHING: AN ANALYTICAL REVIEW - Turdiyeva Zahro Mirsoliyevna (PEDAGOGS, 2025)
This article explores the Direct Method in teaching English, focusing on its origins, key contributors, principles, and practical applications in English as a Foreign Language (EFL) classrooms. The method emphasizes immersive language learning without translation, promoting intuitive communication and inductive grammar instruction. The paper also highlights research findings that underscore its effectiveness in enhancing speaking and listening skills. By analyzing its historical development and classroom techniques, this study offers insights into how the method has shaped modern language teaching practices.